PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP CUSTOMER SATISFACTION DAN REPURCHASE INTENTION PENGGUNA APLIKASI OVO - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2019)
The purpose of this study was to determine the effect of perceived usefulness and perceived ease of use on customer satisfaction and repurchase intention. The sample of this research is OVO users in the Grab application who have done top-up at least 2 times in the Kebumen area as many as 100 respondents. The sampling technique uses nonprobability sampling technique, namely purposive sampling. Methods of data collection using questionnaires, literature studies and interviews. Analysis of the data used is the instrument validity and reliability test, the classic assumption test, hypothesis testing and path analysis using the SPSS 21 program for windows. The results of this study indicate that all items of each variable are valid and reliable. Both structural models meet the classic assumption test criteria with no multicollinearity, heterokedasticity, and normality assumptions. Based on the results of the t test showed that the variable perceived usefulness and perceived ease of use have a significant effect on customer satisfaction, perceived usefulness has a significant effect on repurchase intention, perceived ease of use has a significant effect on repurchase intention, customer satisfaction has a significant effect on repurchase intention.